Design and Control of Standalone PV System without ESD Usage for Enhanced Energy Utilization - Tomar, Anuradha (Recent Advances in Electrical & Electronic Engineering, 2020)
Background: A Standalone Photovoltaic (PV) based system has practical constraints like the need for Energy Storage Devices (ESD) in order to ensure 24 hours availability of electricity and optimized usage of available PV power. Implementation of hybrid renewable energy based system depends upon geographical location and thus availability of a specific energy resource. Also, ESDs are costly to maintain and thus limited optimized usage of ESD is suggested in the literature. Methods: In this paper, a new concept of a PV system integrated with pumped storage is presented for electrification/implementation in rural areas. Proposed system operates at Maximum Power Point Tracking (MPPT) without de-rating the PV capacity or any need of ESD. The control philosophy is simple, robust and ensures two modes of operation for pumped storage i.e. motoring mode and generating mode; depending upon the PV power being generated, load demand and available water level in lower and upper reservoir. Results: The effectiveness of the proposed system and control architecture is verified through MATLAB/Simulink simulation. For various modes of operation, the proposed system is able to maintain DC bus voltage, AC 3-phase voltage, the frequency at approximately constant desired values. Conclusion: However, to operate the PV system at night with heavy loads, additional ESD may be required for better response and stability.
Keywords: High rise building